Salivary Function and Oral Health Problems in Crohn's Disease Patients. Issue 6 (26th April 2018) - de Vries, Silvia A G; Tan, Christopher X W; Bouma, Gerd; Forouzanfar, Tim; Brand, Henk S; de Boer, Nanne K
Abstract: Background: In Crohn's disease (CD) patients, many oral complaints have been reported. The aim of this study was to determine whether salivary function is contributing to reduced oral health in CD. Oral and dental complaints in patients were explored. The prevalence of xerostomia in conjunction with salivary flow rates and biochemical saliva composition was studied. Methods: The Xerostomia Inventory score (XI-score), the salivary flow rates, the concentrations of salivary amylase and mucin 5B, and the type of oral and dental complaints were evaluated. These outcomes were stratified by disease activity, using the Harvey Bradshaw Index (HBI) and the Inflammatory Bowel Disease Questionnaire (IBDQ-9). Results: Fifty-three CD patients in a Dutch tertiary referral hospital were included. Of the patients evaluated, 9.4% had hyposalivation under resting conditions, and 28.3% had hyposalivation under chewing stimulated conditions. Saliva secretion rates were not correlated to XI-scores. Median XI-score was 25 (11–45). XI-scores were correlated to the IBDQ scores (r = −0.352, P = 0.010). Salivary mucin 5B was correlated to disease activity (r = 0.295, P = 0.04). Regarding the number of oral complaints, a correlation with disease activity (HBI r = 0.349, P = 0.011) and experienced xerostomia (r = −0.554, P = 0.000) was observed. Oral and dental problems like oral ulcers (37.7%) and cavities (46%) occurred more frequently in CD patients, especially when compared with a non-IBD population. Conclusions: Oral and dental complaints are common in CD patients. Xerostomia is correlated with disease activity–associated quality of life and with the number of oral and dental complaints. Changes in salivary function may contribute to reduced oral health in CD patients.